PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN APPLIKASI KAKAOTALK - hasjim, munirah; Yang En Siem, Evelyn (JURNAL ILMU BUDAYA, 2021)
Learning activities during the Covid 19 pandemic in 2020 were addressed with various innovations and creativity among teachers. The use of technology media makes the learning process active and students motivated. This classroom research was conducted by applying the Flipped Classroom learning model assisted by the Kakaotalk application and other learning media to determine the effectiveness of this model in increasing student learning interactions in Elementry Level Indonesian Speaking and Listening courses at the Department of Malay-Indonesia Translation and Interpretation of the Hankuk University of Foreign. Korean Studies. The results show that the application of the Flipped Classroom model can improve student interaction skills in speaking and listening to Indonesian material well because they have carried out intensive learning activities outside of online classes, namely using the Kakaotalk application in communicating between students and between teachers.